Glenohumeral range of motion deficits and posterior shoulder tightness in throwers with pathologic internal impingement - Myers, J. B.; Laudner, K. G.; Pasquale, M. R.; Bradley, J. P.; Lephart, S. M. (The American Journal of Sports Medicine, 2005)
Alterations in glenohumeral range of motion, including increased posterior shoulder tightness and glenohumeral internal rotation deficit that exceeds the accompanying external rotation gain, are suggested contributors to throwing-related shoulder injuries such as pathologic internal impingement. Yet these contributors have not been identified in throwers with internal impingement.